EVALUASI KESESUAIAN LAHAN DAN KELAYAKAN EKONOMI TANAMAN KAKAO DI KECAMATAN GANTARANG KEKE KABUPATEN BANTAENG - Wahyuni Mustaman; Amir Tjoneng; Abdullah Abdullah (Percetakan Umi Toaha Makassar, 2019)
The potential of a land for certain uses can be predicted through land evaluation activities. This study aims to 1) evaluate the suitability of the land, 2) analyze the limiting factors and land improvement measures, and 3) analyze the economic feasibility of cocoa plant development carried out in Gantarangkeke, Bantaeng district during April to October 2018. This study uses a parametric approach with qualitative and quantitative mixed methods, field surveys using purposive sampling, biophysical land suitability analysis using a parametric approach (Sys et al., 1991) while economic analysis analyzes the economic feasibility equivalent of rice consumption according to Sajogyo (1977) with rice consumption needs in the village is 320 kg/year and the income-cost ratio (R/C). The result of the study shows that the climate type of the study area according to Schmidt-Ferguson is classified as B (wet) with the actual cocoa land suitability class classified as marginal (S3) and not suitable at this time (N1) with climate limiting factors (relative air humidity) where corrective actions cannot taken, soil physical characteristic (soil depth and coarse fragments) which cannot be corrected, and soil fertility (c-organic) with the addition of organic materials. The average income of farmers that classified class S3 is Rp. 13.901.650/th and N1 is Rp. 7.656.600/th, therefore the research area has a decent life if it the family that classified class S3 with size consists of 4 person with total expenditure of Rp. 12.800.000 and N1 with size consists of 2 person with total expenditure of Rp. 6.400.000. In 2017, income per capita of Bantaeng district is Rp. 856.592 that classified class S3 with size consists of 4 person is Rp. 3.426.368 and N1 with size consists of 2 person is Rp. 1.713.184 with the value of the R-C ratio ranging from 3.40 to 4.90, which means that it is feasible to develop cocoa plants in Gantarangkeke Subdistrict since the R/C value still greater than 1.